DTPA Treatment of Wound Contamination in Rats with Americium: Evaluation of Urinary Profiles Using STATBIODIS Shows Importance of Prompt Administration. Issue 6 (June 2021) - Lamart, Stephanie; Van der Meeren, Anne; Coudert, Sylvie; Baglan, Nicolas; Griffiths, Nina M.
Abstract : Abstract: In the nuclear industry, wound contamination with americium is expected to increase with decommissioning and waste management. Treatment of workers with diethylenetriaminepentaacetic acid (DTPA) requires optimization to reduce internal contamination and radiation exposure. This work aimed at evaluating and comparing different DTPA protocol efficacies after wound contamination of rats with americium. Wound contamination was simulated in rats by depositing americium nitrate in an incision in the hind limb. Different routes, times, and frequencies of DTPA administration were evaluated. Individual daily urinary americium excretion and tissue retention were analyzed using the statistical tool STATBIODIS. Urinary profiles, urinary enhancement factors, and inhibition percentages of tissue retention were calculated. A single DTPA administration the day of contamination induced a rapid increase in americium urinary excretion that decreased exponentially over 7 d, indicating that the first DTPA administration should be delivered as early as possible. DTPA treatment limited americium uptake in systemic tissues irrespective of the protocol. Liver and skeleton burdens were markedly reduced, which would drive reduction of radiation dose. Local or intravenous injections were equally effective. Inherent difficulties in wound site activity measurements did not allow identification of a significant decorporating effect at the wound site. Repeated intravenous injections of DTPA also increased americium urinary excretion, which supports the use of multiple DTPA administrations shortly after wound contamination. Results from these statistical analyses will contribute to a better understanding of americium behavior in the presence or absence of DTPA and may aid optimization of treatment for workers. Abstract : Supplemental digital content is available in the text.